The sulfur budget of the 2011 Grímsvötn eruption, Iceland - Sigmarsson, Olgeir; Haddadi, Baptiste; Carn, Simon; Moune, Séverine; Gudnason, Jonas; Yang, Kai; Clarisse, Lieven (Geophysical Research Letters, 2013)
International audience Sulfur concentrations have been measured in 28 melt inclusions (MIs) in plagioclase, clinopyroxene, and olivine crystals extracted from tephra produced during the explosive eruption of Grímsvötn in May 2011. The results are compared to sulfur concentrations in the groundmass glass in order to estimate the mass of sulfur brought to surface during the eruption. Satellite measurements yield order of magnitude lower sulfur (~0.2 Tg) in the eruption plume than estimated from the difference between MI and the groundmass glass. This sulfur "deficit" is readily explained by sulfur adhering to tephra grains but principally by sulfide globules caused by basalt-sulfide melt exsolution before degassing. A mass balance calculation reveals that approximately ~0.8 Tg of SO2 is present as globules, representing ~50% of the total sulfur budget. Most of the sulfide globules likely reside at depth due to their elevated density, for potential later remobilization by new magma or hydrothermal circulation.